Kinesin, 30 years later: Recent insights from structural studies - Wang, Weiyi (Protein Sci, 2015)
Motile kinesins are motor proteins that move unidirectionally along microtubules as they hydrolyze ATP. They share a conserved motor domain (head) which harbors both the ATP- and microtubule-binding activities. The kinesin that has been studied most moves toward the microtubule (+)-end by alternately advancing its two heads along a single protofilament. This kinesin is the subject of this review. Its movement is associated to alternate conformations of a peptide, the neck linker, at the C-terminal end of the motor domain. Recent progress in the understanding of its structural mechanism has been made possible by high-resolution studies, by cryo electron microscopy and X-ray crystallography, of complexes of the motor domain with its track protein, tubulin. These studies clarified the structural changes that occur as ATP binds to a nucleotide-free microtubule-bound kinesin, initiating each mechanical step. As ATP binds to a head, it triggers orientation changes in three rigid motor subdomains, leading the neck linker to dock onto the motor core, which directs the other head toward the microtubule (+)-end. The relationship between neck linker docking and the orientations of the motor subdomains also accounts for kinesin's processivity, which is remarkable as this motor protein only falls off from a microtubule after taking about a hundred steps. As tools are now available to determine high-resolution structures of motor domains complexed to their track protein, it should become possible to extend these studies to other kinesins and relate their sequence variations to their diverse properties.